Cinobufotalin injection combined with chemotherapy for the treatment of advanced NSCLC in China: A PRISMA-compliant meta-analysis of 29 randomized controlled trials. Issue 35 (August 2019) - Zhang, Fan; Yin, Yantong; Xu, Tiantian
Abstract: Background and objective: Cinobufotalin injection (CFI), a kind of Chinese medicine, has been considered as a promising complementary therapy option for advanced non-small cell lung cancer (NSCLC), but their efficacy and safety remain controversial. This study aimed to systematically evaluate the efficacy and safety of CFI and chemotherapy-combined therapy for advanced NSCLC. Methods: Clinical trials were searched from Web of Science, Cochrane Library, PubMed, Embase, China National Knowledge Infrastructure (CNKI), Chinese Biological Medicine Database (CBM), Chinese Medical Citation Index (CMCI), Wanfang database and Chinese Scientific Journal Database (VIP). Main measurements, including therapeutic efficacy, quality of life (QoL) and adverse events, were extracted from the retrieved publications and were systematically evaluated. Results: The 29 trials including 2300 advanced NSCLC patients were involved in this study. Compared with chemotherapy alone, its combination with CFI significantly prolonged the patients' 1-, 2- and 3-year overall survival rate (OS) (1-year OS, OR = 1.94, 95% CI = 1.42–2.65, P < .0001; 2-year OS, OR = 2.31, 95% CI = 1.55–3.45, P < .0001; 3-year OS, OR = 4.69, 95% CI = 1.78–12.39, P = .002) and improved patients' overall response (ORR, OR = 1.84, CI = 1.54–2.18, P < .00001), disease control rate (DCR, OR = 2.09, 95% CI = 1.68–2.60, P < .00001) and QoL (quality of life improved rate, QIR, OR = 2.64, 95% CI = 1.98–3.52, P < .00001; karnofsky performance score, KPS, OR = 10.97, 95% CI = 5.48–16.47, P < .0001). Most adverse events caused by chemotherapy were obviously alleviated ( P < .05) when CFI was also applied to patients. Conclusion: The combination of CFI and chemotherapy is safe, and is more effective in treating NSCLC than chemotherapy alone. Therefore, CFI mediated therapy could be recommended as an adjuvant treatment method for NSCLC. Abstract : Supplemental Digital Content is available in the text